Tecnologias para o mapeamento e enfrentamento da violência escolar na Paraíba - Santos Júnior, Francisco Ribeiro dos (2023)
In the era of society 5.0, we can identify a set of efforts that seek to build a harmonious convergence between technological advances and human well-being, providing an improvement in our quality of life through artificial intelligence and data analysis, for example. Alongside the latest advances, our contemporary reality faces a frightening challenge, which raises concerns and apprehensions: a growing incidence of violence in the school environment. Given the above, with this research we seek to investigate conceptual bases for prototyping a system for mapping and coping with school violence and bullying in Paraíba. It is a research that seeks in technologies, a probable response to the incidence of school violence and bullying in educational institutions in Paraíba, which can be replicated in the future throughout Brazil. This is an exploratory study, in the form of a qualitative bibliographical research, whose methodological path begins with the investigation of school violence in Paraíba; it goes through the search for technological tools for mapping and coping with school violence and stops at the conception of a prototype system to help in mapping and coping with school violence. The results showed that, despite very objective legislation on this issue, there is a lack of structured data on school violence in the state of Paraíba, making it difficult to build a typology of these acts, as well as the implementation of coping strategies. The injuries suffered were permeated by valid, but very specific, parts of mapping and coping with school violence and bullying. Finally, the essential requirements that support the development of SIMOVE: School Violence Monitoring System are presented, discussed and prototyped.